The Western Balkans without a plan for the future: The EU expansion debate threatens the stability of Europe's weakest region - Dušan Reljić (Stiftung Wissenschaft und Politik (SWP), 2005)
The recent debacle surrounding the EU's draft constitution and the subsequent calls by some member states for either a delay or even a halt altogether of future EU expansion could well undermine the precarious stability of the Western Balkans. The fading perspective of EU membership has already had consequences: nationalist voices are growing louder again and in foreign relations a distinct turn toward the US is evident. In Croatia, which is the closest in the region to attaining EU membership, it is only now every third citizen that backs the country's membership in the EU. In order to avert rekindling ethno-political conflicts, and to retain the credibility of Europe's Common Foreign and Security Policy as well, the EU should lay out a clear roadmap and the conditions for the next round of expansion. (SWP Comments / SWP)
Keywords: 320